The Variability of Platelet-Collagen Interaction. Its Influence on Aspirin-Induced Inhibition of Platelet Aggregation - Sack, E. S; Quiroga, E (Thrombosis and Haemostasis, 1976)
A study of platelet aggregation induced by progressive concentrations of collagen was performed in 40 normal persons, equally grouped by sex, immediately before, and 90 min after, the ingestion of 0.500 g aspirin. Simultaneously, serum ASA-esterase activity and plasmatic salicylic acid levels were investigated in the pre- and post-ASA samples respectively. Wide individual variations in platelet responsiveness to collagen were found when the minimal amount of the aggregating agent necessary to provoke significant aggregation was located. The percentage of aggregation and the slope were the most sensible indicators of both the individual variances and the ASA-induced inhibition. Correlation was found in both groups between the minimal amounts of collagen required for initiating aggregation pre- and post-ASA. Also a positive correlation was found between the minimal collagen concentration required to initiate aggregation pre-ASA and the aspirin-induced inhibition in the aggregation produced by a higher collagen concentration. Important individual and sexual differences were detected in the serum content of ASA-esterase activity. A negative significant correlation was demonstrated between the ASA-esterase activity and the differences in collagen concentrations necessary to start aggregation pre- and post-aspirin in the men group. Failure to consider individual variances in platelet reactivity may lead to false conclusions about the ASA affective-ness as an antithrombotic agent.